2016
DOI: 10.1002/ece3.1896
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative shifts in defensive metabolites define chemical defense investment during leaf development inInga, a genus of tropical trees

Abstract: Selective pressures imposed by herbivores are often positively correlated with investments that plants make in defense. Research based on the framework of an evolutionary arms race has improved our understanding of why the amount and types of defenses differ between plant species. However, plant species are exposed to different selective pressures during the life of a leaf, such that expanding leaves suffer more damage from herbivores and pathogens than mature leaves. We hypothesize that this differential sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 71 publications
3
44
0
1
Order By: Relevance
“…Most often, rainforest plants do not have expanding leaves, restricting chemocoding to a minority of saplings at any given point in time and reducing the utility of chemocoding. We found that mature leaves have most, but not all, of the chemical signals found in expanding leaves (Lokvam et al ., ; Wiggins et al ., ), so the use of mature leaves should be feasible. Additionally, we used UPLC with a 150‐mm column, followed by detection with a high‐resolution time‐of‐flight mass spectrometer, an expensive analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, rainforest plants do not have expanding leaves, restricting chemocoding to a minority of saplings at any given point in time and reducing the utility of chemocoding. We found that mature leaves have most, but not all, of the chemical signals found in expanding leaves (Lokvam et al ., ; Wiggins et al ., ), so the use of mature leaves should be feasible. Additionally, we used UPLC with a 150‐mm column, followed by detection with a high‐resolution time‐of‐flight mass spectrometer, an expensive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For each species, samples of expanding leaves were collected from five saplings, 0.5-4 m in height, in the shaded understory. We focused on expanding leaves as part of a study of plant-herbivore interactions and also because secondary metabolites are at greater concentration during the expansion stage than in leaves that have matured and toughened (Wiggins et al, 2016). For each sapling, we collected leaves that were between 20% and 80% of the average maximum size.…”
Section: Collectionsmentioning
confidence: 99%
“…The methodology described below is specific for extracting secondary soluble metabolites (no primary metabolites were extracted nor analyzed). Those compounds covalently bound to the cell wall were also excluded (Endara et al, ; Wiggins, Forrister, Endara, Coley, & Kursar, ). Preliminary chromatographic analyses were performed to detect the optimal number of samples required for chemical analyses (Supporting Information Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, there is strong selection to invest in chemical defences, and in Inga, secondary metabolites comprise over 50% of the dry weight of expanding leaves. Once the leaf is full size and can toughen, investment drops by more than half (Wiggins, Forrister, Endara, Coley, & Kursar, 2016).…”
Section: Introductionmentioning
confidence: 99%